Atomically Precise Engineering of Single‐Molecule Stereoelectronic Effect. (26th April 2021) - Meng, Linan; Xin, Na; Wang, Jinying; Xu, Jiyu; Ren, Shizhao; Yan, Zhuang; Zhang, Miao; Shen, Cheng; Zhang, Guangyu; Guo, Xuefeng; Meng, Sheng
Abstract: Charge transport in a single‐molecule junction is extraordinarily sensitive to both the internal electronic structure of a molecule and its microscopic environment. Two distinct conductance states of a prototype terphenyl molecule are observed, which correspond to the bistability of outer phenyl rings at each end. An azobenzene unit is intentionally introduced through atomically precise side‐functionalization at the central ring of the terphenyl, which is reversibly isomerized between trans and cis forms by either electric or optical stimuli. Both experiment and theory demonstrate that the azobenzene side‐group delicately modulates charge transport in the backbone via a single‐molecule stereoelectronic effect. We reveal that the dihedral angle between the central and outer phenyl ring, as well as the corresponding rotation barrier, is subtly controlled by isomerization, while the behaviors of the phenyl ring away from the azobenzene are hardly affected. This tunability offers a new route to precisely engineer multiconfigurational single‐molecule memories, switches, and sensors. Abstract : Precise control of the dihedral angle and the rotation processes of phenyl rings of a prototype terphenyl molecule can be achieved by introducing a photochromic molecule, azobenzene, as the side chain. The experimental and theoretical data demonstrate that the structure of the side chain can alter the twisted angle of adjacent phenyl rings, as well as the rotation barrier, because of the variable steric hindrance of the azobenzene group.